KESIAPAN GURU DALAM IMPLEMENTASI ASESMEN KOMPETENSI MINIMUM PADA PEMBELAJARAN EKONOMI - Rika Dwi Safitri; Yosia Dian Purnama Windrayadi; Muhammad Yusuf (Universitas Muhammadiyah Metro, 2024)
Penelitian ini bertujuan untuk mengetahui: (1) kesiapan guru dalam menghadapi asesmen kompetensi minimum, (2) kesiapan guru dalam menghadapi survei karakter, (3) kesiapan guru dalam menghadapi survei lingkungan belajar. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian deskriptif kualitatif dengan metode eksplanatori. Data yang diambil yaitu data kualitatif dengan informan penelitian adalah beberapa guru di sekolah SMA di Kota Tuban yang berjumlah 5 orang Hasil penelitian menunjukan bahwa guru sudah memahami AKM dilihat dari kemampuan guru membuat komponen-komponen dalam penyusunannya. Kesiapan guru juga sudah cukup dalam menghadapi AKM pada tahun 2024. This study examines teachers' readiness to implement the Minimum Competency Assessment (AKM) within the Merdeka Curriculum. Teachers face challenges adapting to the new assessment method due to the numerous instruments that need to be completed and the similarity of indicators, which often leads to errors. The study aims to determine teachers' readiness, supporting factors, and obstacles in conducting AKM, particularly in economics education. A qualitative approach with a descriptive research type and grounded theory method was employed. The research involved three teachers from SMAN 2 Tuban as informants. The results show that teachers understand AKM, especially when preparing its components. However, several obstacles were identified, including issues with electricity and internet networks, the readiness of AKM committees, and limited time to comprehend the assessment questions.